International Studies in the Philippines: Mapping New Frontiers in Theory and Practice, 1st edition - Cruz, Frances Antoinette (Routledge, 2020)
How can local experiences and the social transformation generated by modernity help to enrich our understanding of the international? What might a version of the much-discussed "non-Western International Relations (IR)" look like? What continuities and discontinuities from the Philippine experience in particular can be useful for understanding other post-colonial polities?